Direct observation of trap-assisted recombination in organic photovoltaic devices - Stefan Zeiske (Nature Portfolio, 2021)
Trap-assisted recombination caused by localised sub-gap states is one of the factors limiting power-conversion efficiency in solar cells, yet the presence and relevance is still under debate in organic solar cells. Here, the authors reveal that this recombination loss is universally present under operational conditions in these devices.